Estimasi Persentase Karbon Organik Di Hutan Mangrove Bekas Tambak, Perancak, Jembrana, Bali - Mahasani, I Gusti Agung Indah; Widagti, Nuryani; Karang, I Wayan Gede Astawa (Journal of Marine and Aquatic Sciences; Vol 1 No 1 (2015), 2015)
Mangrove forests in the coastal regions are very effective and efficient in reducing the concentration carbon dioxide (CO2) in the atmosphere, because mangroves can absorb CO2 through photosynthesis by diffusion through the stomata and then store carbon in the form of biomass. The purpose of this study, namely: (1) Determine the percentage of organic carbon in the soil in former mangrove forest ponds in Perancak and (2) Determine the vertical variation of the percentage of organic carbon stored in soils in former mangrove forest ponds in Perancak. The method used from this study is the loss on ignition (LOI). The average percentage of organic carbon in mangrove forest area of the former farm of 50.181 % C or 184.618 Mg/ha. The average vertical variations of each depth, that is: depth (0-15 cm) 50.487 % C, (15- 30 cm) 50.781 % C, (30-50 cm) 50.550 % C, (50- 100 cm) 51.689 % C, and (> 100 cm) 47.396 % C.
Keywords: former mangrove forest ponds; organic carbon stored